Effects of VEGF inhibitors on human retinal pigment epithelium under high glucose and hypoxia. (22nd July 2019) - Bahrami, Bobak; Shen, Weiyong; Zhu, Ling; Zhang, Ting; Chang, Andrew; Gillies, Mark C.
Abstract: Background: Retinal pigment epithelium (RPE) is known to secrete factors important for retinal homeostasis. How this secretome changes in diabetic eyes treated with anti‐vascular endothelial growth factor (VEGF) inhibitors is unclear. Methods: Diabetic conditions were simulated in vitro using ARPE‐19 cell‐line culture, with high glucose (25 mM) culture media, and hypoxia was chemically induced using cobalt chloride. Stress was assessed using cell viability assays as well as Western blots and enzyme‐linked immunosorbent assay (ELISA) for production of HIF‐1a and VEGF‐A. Production of neurotrophic factors was quantified once conditions were established using ELISA under stress with and without the addition of VEGF inhibitors. Changes were analysed with one‐way ANOVA. Results: Hypoxia downregulated pigment epithelium‐derived factor (PEDF) expression. The addition of bevacizumab, ranibizumab and aflibercept in normoxic conditions all led to a significant downregulation of PEDF. Glucose concentration had no effect on secretion of PEDF. Brain‐derived neurotrophic factor (BDNF) secretion was downregulated in high glucose and was upregulated in hypoxia. Placental growth factor (PlGF) secretion by ARPE‐19 was undetectable by ELISA. Conclusions: We found that hypoxia, high glucose or VEGF inhibitors affected secretion of neurotrophic factors. This variation under different conditions may influence neuron and photoreceptor survival in the diabetic state and VEGF inhibitor treated eyes.